BiCMOS based self-calibrated current cells for high precision digital to analog converters - Leung, B.H. (IEEE International Symposium on Circuits and Systems, 1992, 1992)
Self-calibrated current cells for high precision D/A (digital to analog) converters that rely on CMOS technology are subject to limitations such as charge injection and finite output resistance. Two new current cells based on BiCMOS technology that attempt to overcome these problems are presented. The cell with a CMOS output transistor, denoted as the type I current cell, offers a significant reduction in charge injection and leakage current. The cell with a bipolar output transistor, denoted as the type II current cell, offers a higher R/sub out/, larger available voltage swing, and faster switching. In addition, when compared to previous bipolar-based current cells employing equal-value current sources, the type II cells does not need emitter degeneration resistors. HSPICE simulation results show that the proposed circuits can achieve up to a factor of two improvement in accuracy, for the same mismatches, over previously reported results.< >